The European energy crisis - Åslund, Anders (Henry Stewart Talks, 2023)
Energy crisis, Pipe gas, EU, Liquified natural gas (LNG), LNG terminals, Russia, Germany, National-level policy, Fukushima, Poland, Lithuania, National security, Nord Stream, Unbundling